A survey of GNSS interference monitoring technologies - Qiao, Jia; Lu, Zukun; Lin, Baojun; Song, Jie; Xiao, Zhibin; Wang, Zhi; Li, Baiyu (Frontiers in Physics, 2023)
With the increasing economic and strategic significance of the global navigation satellite systems (GNSS), interference events also occur frequently. Interference monitoring technology aims to monitor the interference that may affect the regular operation of the GNSS. Interference monitoring technology can be divided into three parts: interference detection and recognition, interference source direction finding, interference source location and tracking. Interference detection aims to determine whether interference exists. This paper introduces the classification of interference and the corresponding detection methods. The purpose of interference recognition is to recognize and classify the interference. It is often combined with pattern recognition and machine learning algorithms. Interference source direction finding aims to estimate the direction of the interference signal. There are three kinds of methods: amplitude method, phase method, and spatial spectrum estimation method. Interference source location aims to estimate the position of the interference signal. It is usually based on received signal strength (RSS), time difference of arrival (TDOA), frequency difference of arrival (FDOA), Angle of arrival (AOA) or direction of arrival (DOA). Interference source tracking aims to track the moving interference sources, and it is generally based on Kalman filter theory. This paper summarizes the interference monitoring technology and its latest progress. Finally, a prospect for the interference monitoring technology is offered.